Evaluating the Management Effectiveness of the Marine Tourism Park in Eastern Bintan Island, Indonesia - Bagus Bagaskoro; Eka Intan Kumala Putri; Wonny Ahmad Ridwan (Journal of Natural Resources and Environmental Management)
Marine Tourism Park in the Eastern Region of Bintan Island (Bintan MPA) is located in Bintan Regency, Riau Islands Province. This marine protected area (MPA) covers a total area of 1,385.61 km2. In 2014, due to the implementation of a new government law, the management authority of this MPA changed, resulting in its institutional redesign. The process was completed in April 2022. As a new MPA, the management activities have not been carried out optimally because the management resources were still limited. Thus, this research aims to evaluate the management effectiveness of Bintan MPA. The research was conducted in the Bintan MPA and took place from October 2021 to October 2022. Informants involved in this research were selected using purposeful sampling and snowball sampling method. The data collection methods were interviews (structured and in-depth) and document verification. EVIKA assessment was used for data analysis. There were four criteria assessed: input, process, output, and outcome, each with several indicators. The percentage results of each criterion were 79.53%, 34.88%, 21.54%, and 27.20%, respectively. The final percentage of the EVIKA assessment was 41.56%, with an effectiveness status of "minimally managed" and a "bronze" label. This means that the conservation area design and management process had been carried out, but efforts were still needed to achieve the management goals.